Exploration of the Practice of Curriculum Reform in Chinese Vocational Education - Lianlong Zhang; Cheng Cai; Shifang Xu (Tecno Scientifica Publisher, 2026)
In secondary vocational education, the coherence and connection of curriculum content are crucial for students’ holistic development. This study focused on the logistics major in vocational schools and applied Pearson correlation coefficients to analyze learning transfer effects between courses, providing data-based support for curriculum design and integration. The results showed that among the three basic courses of language arts, mathematics, and English, mathematics demonstrated the strongest internal coherence. The high correlation among specialized courses indicated that their arrangement was more conducive to systematic and in-depth knowledge acquisition. Variations in correlation coefficients over time provided a basis for optimizing early course planning, strengthening academic early warning mechanisms in vocational schools, preventing academic difficulties, and ensuring a smooth and effective learning process for students.